EVALUASI KELAYAKAN GEDUNG NEGARA (BPBD PAGAR ALAM) DENGAN METODE DaLA - Norma Puspita (Jurnal Tekno Global, 2016)
According to Law Decree No. 28 of 2002 that the building is important as a man carries out its activities in order to achieve various objectives that support the realization of national development goals. Given the importance of the office building, the construction of office buildings should be viewed from several sides. These include a review of the feasibility of the construction of the building, in conjunction denagan classification of office buildings in accordance with the level of service and the ability to receive the load. Unlike the construction of private buildings in which the amount of revenue per year from the building in question can be calculated, whereas in building the State, the value of the advantages seen from the benefits received by the public of the existence of the building and the performance of the agency, the profit received by the government or the State are social benefits itangible. This study aimed to evaluate the feasibility of building the State BPBDs Pagar Alam based disaster mitigation management. The method used in this study using spatial analysis, DaLA (Damage and Loss Assessment), and the method of SWOT (Strength, Weakness, Opportunities, and Threats) analysis to determine the feasibility of recommendations for the construction of state buildings. The results of the feasibility analysis of investment based methods DaLA known that the payback period occurred in the year to 8 under the assumption that acceptance comes from the local budget, while expenditure is the amount of compensation issued by the State disaster. Based on the analysis of spatial planning both sites located outside the district administrative center. Meanwhile, if viewed from the analysis of disaster-prone building at the site suggested BPBDs Atung Youngest who are outside the danger zone of the mountain api.berdasarkan SWOT analysis is known that the location in the Village of Ulu Rurah more recommended for building construction BPBDs. Keywords : Feasibility, the State House, DaLA, SWOT